ANALISIS KINERJA SUPPLIER BERDASARKAN PENDEKATAN VENDOR PERFORMANCE INDICATOR (VPI) MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS(AHP) DI PT. IDELUX FURNITURE INDONESIA - Irwan Sukendar; Wiwiek Fatmawati; Akmal Frinzani (Jurnal Ilmiah Dinamika Teknik, 2021)
PT. Idelux Furniture Indonesia is a manufacturing company engaged in the production of furniture, which produces chairs and tables. The main raw materials for the manufacture of this product are aluminum, woven materials, fabrics and foam. These raw materials come from both foreign and domestic suppliers. The problems that often occur at PT. Idelux Furniture Indonesia, namely in terms of raw materials, prices, quality, and delays when the delivery process does not match. The purpose of this study is to evaluate the performance evaluation of suppliers on aluminum raw materials, so that the company can find out which supplier has the best performance. There are several criteria and sub-criteria at PT. Idelux Furniture Indonesia, namely the criteria for quality, cost, delivery, flexibility and responsivenees as well as sub-criteria for the quality of raw materials, completeness of certificates, raw material prices, bill payment periods, on time delivery, accuracy in quantity or quantity of raw materials sent, fulfillment of requests for changes in the amount of raw materials ordered, changes in delivery time, response to changes in delivery schedules and suppliers respond to quality problems. From the calculation and weighting of suppliers against 5 criteria and 10 sub-criteria based on the Vendor Performance Indicator approach, it is found that PT. A has the highest value, namely 2.51 then PT. B with a value of 1.65 and the lowest is PT. C 0.83.